Ileal pouch-anal canal anastomosis for familial adenomatous polyposis: early and late results. - Nyam, D C (1997)
OBJECTIVE: The objective was to review the early and late results of ileal pouch-anal anastomosis (IPAA) done for patients with familial adenomatous polyposis (FAP). SUMMARY BACKGROUND DATA: Patients with FAP will have colorectal adenomas develop and die of colorectal cancer if left untreated. Ileal pouch-anal anastomosis removes all disease-bearing mucosa while preserving transanal passage of stools. METHODS: Between 1981 and 1994, 187 patients with FAP, 11 to 59 years of age with a mean follow-up of 60 months (range, 5-170 months) had proctocolectomy and IPAA at Mayo Medical Center in Rochester, Minnesota. All patients had a proximal anal canal mucosal excision and a hand-sewn anastomosis of the pouch to the anal canal at the dentate line. A temporary ileostomy was used in 85% of the patients. RESULTS: No early postoperative deaths occurred, although two patients died later of metastatic colorectal carcinoma present at their initial operation. More important, no patient had a new cancer develop after IPAA. The overall morbidity after operation was 24%, with small bowel obstruction being the most common complication (13%). Patients had four bowel movements/24 hours and good fecal control, which continued during follow-up. CONCLUSIONS: The IPAA eradicates the risk of colorectal cancer in patients with FAP. It can be performed with low mortality, acceptable morbidity, and good functional results over the long term.